2019
DOI: 10.3390/ijerph16071154
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Microorganisms on Nonwovens Used for the Construction of Filtering Facepiece Respirators

Abstract: Filtering nonwovens that constitute the base material for filtering facepiece respirators (FFRs) used for the protection of the respiratory system against bioaerosols may, in favourable conditions, promote the development of harmful microorganisms. There are no studies looking at the impact that different types of filtering nonwovens have on microorganism survival, which is an important issue for FFR producers and users. Five commercial filtering nonwovens manufactured using diverse textile technologies (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The nonwoven fabric incorporates electrostatic charges and can remove bacteria/viruses and aerosols containing microorganisms by physical filtration and electrostatic absorption when air is permeated through ( Figure 1 a). Majchrzycka and coworkers [ 44 ] investigated the survival of microorganisms on five different commercial filtering nonwoven masks. They found that structural parameters of the tested nonwovens (mass per unit area and thickness) and contact angle changes did not greatly affect microorganism survival, but the survival fraction was more dependent on microorganism species.…”
Section: Mask Application and Development Status: Civil Sanitary Surmentioning
confidence: 99%
“…The nonwoven fabric incorporates electrostatic charges and can remove bacteria/viruses and aerosols containing microorganisms by physical filtration and electrostatic absorption when air is permeated through ( Figure 1 a). Majchrzycka and coworkers [ 44 ] investigated the survival of microorganisms on five different commercial filtering nonwoven masks. They found that structural parameters of the tested nonwovens (mass per unit area and thickness) and contact angle changes did not greatly affect microorganism survival, but the survival fraction was more dependent on microorganism species.…”
Section: Mask Application and Development Status: Civil Sanitary Surmentioning
confidence: 99%
“…Polymers, which act as the primary substrate for face masks, could be fine−tuned to impart bio−active and bio−passive properties to the fabrics. The active moieties such as N−halamines, QACs, PEI, benzophenone (BP), polypyrrole, and inorganic groups, such as metals, have been incorporated to yield various antimicrobial polymers suitable for making a reusable facemask [ 190 , 191 ]. Among these, N−halamine and QACs have proven and powerful activity against a broad spectrum of microorganisms.…”
Section: Asas With Apsmentioning
confidence: 99%
“…Nonetheless, some constraints of nominal standard mask ongoing usages for medical safety purpose. Firstly, the exteriors of surgical masks are hydrophobic, water droplets encompassing terrible viruses can remain on them [21] , [22] . Secondly, the mask has a low diffusing point; commonly lower than 130ºC to 140ºC, so those masks are highly demanding to reiterate them even with the sunlight sterilization techniques avoiding antibacterial coating from the graphene layered mask.…”
Section: Introductionmentioning
confidence: 99%